Issues of Improving Monetary Policy Instruments - Shomurodov Ravshan Tursunkulovich (Zien Journals, 2022)
This article indicates the monetary policy instruments developed over the years under the influence of innovative ideas based on the best practices of developed countries, and examines the scientific and theoretical views of foreign economists in this regard. It is also based on the fact that monetary policy has played an important role in solving financial and economic crises, epidemics, pandemics, macroeconomic and financial problems observed at different periods in the history of world economies. The practice of using monetary policy instruments in Uzbekistan is analyzed, existing problems are identified and their scientific solutions are presented. In turn, science-based scientific, theoretical and practical proposals and recommendations have been developed to increase the role of Uzbekistan in strengthening sustainable economic growth, financial and macroeconomic stability by improving monetary policy
Keywords: monetary policy; monetary instruments; economic growth; macroeconomic sustainability